2010
DOI: 10.1016/j.nutres.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Short-term nutritional folate deficiency in rats has a greater effect on choline and acetylcholine metabolism in the peripheral nervous system than in the brain, and this effect escalates with age

Abstract: The hypothesis of this study is that a folate-deficient diet (FD) has a greater effect on cholinergic system in the peripheral nervous system than in the brain, and that this effect escalates with age. It was tested by comparing choline and acetylcholine levels in male Sprague Dawley rats fed either control or folate-deficient diets for 10 weeks, starting at age 4 weeks (the young group) or 9 months (the adult group). FD consumption resulted in depletion of plasma folate in both age groups. In young folate-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
(83 reference statements)
0
5
1
1
Order By: Relevance
“…Some studies reported that FA concentration had been decreased in the tissues of animals who were fed a FA-free diet for at least 3 wk (16,17). In our study, FA level in the plasma, homocyte, liver and uterus was markedly lower in the FA-deficient group than in the control group at Day 36 (data are not shown).…”
Section: Discussioncontrasting
confidence: 51%
“…Some studies reported that FA concentration had been decreased in the tissues of animals who were fed a FA-free diet for at least 3 wk (16,17). In our study, FA level in the plasma, homocyte, liver and uterus was markedly lower in the FA-deficient group than in the control group at Day 36 (data are not shown).…”
Section: Discussioncontrasting
confidence: 51%
“…Choline and folate are metabolically interrelated and there is growing evidence from both animal (Chew et al, 2011; Craciunescu et al, 2010; Crivello et al, 2010; Field et al, 2013; Kim et al, 1994; Schwahn et al, 2003; Troen et al, 2008; Varela-Moreiras et al, 1995; Zeisel, 2008) and human (Ivanov et al, 2009; Jacob et al, 1999) studies that altering metabolism of one of these nutrients can result in compensatory changes in the other. The present finding that dietary folate deficiency increases expression of CHT1 is consistent with the prior report that maintaining rats on a folate deficient diet for ten weeks increases ACh levels in the frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these results, it seems that learning and memory improving effects of FA seen in the present study are at least in part due to its attenuating effect on AChE activity. It has also been reported that FA de ciency is associated with cholinergic system dysfunction and increased AChE activity (Crivello et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Administration of FA in hypothyroid rats improved oxidative stress and hypothalamic monoamines (Ibrahim et al 2012). In addition, folate is metabolically bound to choline and is involved in the synthesis and release of acetylcholine (Crivello et al 2010). Folate deprivation genetically or in the diet, reduces acetylcholine levels and can affect cognitive activity (Chan et al 2008).…”
Section: Introductionmentioning
confidence: 99%